Research Progress and Trends in Metabolomics of Fruit Trees - Li, Jing; Yan, Guohua; Duan, Xuwei; Zhang, Kaichun; Zhang, Xiaoming; Zhou, Yu; Wu, Chuanbao; Zhang, Xin; Tan, Shengnan; Hua, Xin; Wang, Jing (Frontiers in Plant Science, 2022)
Metabolomics is an indispensable part of modern systems biotechnology, applied in the diseases diagnosis, pharmacological mechanism, quality monitoring of crops, vegetables, fruits etc. Metabolomics of fruit trees has developed rapidly in recent years, and many important research results have been achieved in combination with transcriptomics, genomics, proteomics, QTL and GWAS. These research results mainly focus on the mechanism of fruit quality formation, metabolite markers of special quality or physiological period, the mechanism of fruit tree resistance to biotic / abiotic stress, and the mechanism of fruit population genetics. According to different experimental purposes, different metabolomic strategies could be selected, such as Targeted metabolomics, Non-targeted metabolomics, Pseudo-targeted metabolomics and Widely-targeted metabolomics. This paper presents metabolomics strategies, key techniques in metabolomics, main applications in fruit trees and prospects for the future. With the improvement of instruments, analysis platform and metabolite database, decrease of cost of experiment, metabolomics will prompt the fruit tree research to achieve more breakthrough results.